THE EFFECT OF BALANCE TRAINING ON THE LEVEL OF PHYSICAL ACTIVITY IN PATIENTS WITH MULTIPLE SCLEROSIS (Physical Culture and Sport: Scientific Perspective, 2025)
Multiple sclerosis is a neuroinflammatory disease that leads to progressive neurodegeneration and a wide range of functional system disorders, and is the most common non-traumatic neurological cause of disability in young people. Reduced physical activity is one of the common consequences of multiple sclerosis, which worsens the prognosis for secondary complications and disability. Balance disorders are among the factors that lead to a decrease in physical activity in multiple sclerosis, but there is a lack of research on the effectiveness of different methods of balance training on physical activity in this population. The aim of the study: to evaluate the effect of different methods of balance training on physical activity in patients with multiple sclerosis. Material and Methods: 57 patients with multiple sclerosis participated in the study and were randomized into two groups: the intervention group (29 people) and the comparison group (28 people). The intervention group implemented a physical therapy program using the neuromuscular activation method, while the comparison group used conventional balance exercises. The study participants were examined twice: the first time - before the start of physical therapy, the second time - 21 days after the start of the intervention. The International Physical Activity Questionnaire was used to assess the outcome indicators. Evaluation of the effectiveness of the physical therapy program using the neuromuscular activation technique demonstrated a statistically significant larger effect size for the physical activity index in the intervention group compared to the group in which conventional balance exercises were used, and also contributed to more pronounced clinically significant changes in the physical activity index in patients with multiple sclerosis.
Keywords: multiple sclerosis; physical therapy; physical activity; balance; rehabilitation; neuromuscular activation